2015
DOI: 10.1007/s00228-015-1813-3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of linezolid treatment using intravenous and oral administrations in extremely premature infants

Abstract: This study reports an adequate linezolid plasma concentration with regard to the linezolid MIC in extremely premature infants. However, considering adverse events reported, its use should be cautious and may concern only oral administration during the late phase of infection, to limit paradoxical catheter use to treat nosocomial infections. Moreover, safe and efficient anti-Staphylococcus therapies should be identified to treat this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…In a retrospective study, five preterm infants (GA 28 ± 3.5 weeks), treated for late-onset sepsis, who experienced renal failure, switched from iv vancomycin (30 mg/kg/day) to oral linezolid (30 mg/kg/day q8h). C max for all patients but one was above the measured MIC for the causative pathogen 33 …”
Section: Resultsmentioning
confidence: 72%
“…In a retrospective study, five preterm infants (GA 28 ± 3.5 weeks), treated for late-onset sepsis, who experienced renal failure, switched from iv vancomycin (30 mg/kg/day) to oral linezolid (30 mg/kg/day q8h). C max for all patients but one was above the measured MIC for the causative pathogen 33 …”
Section: Resultsmentioning
confidence: 72%
“…Thanks to its wide bacterial spectrum, including Gram-positive bacteria and its excellent bioavailability, linezolid emerged in the early 2000s as a good alternative to vancomycin. In the speci c population of neonates, literature data dealing with linezolid pharmacology, safety, effectiveness and tolerance in neonates is exponential thus demonstrating its growing importance (6,8,9,13). In the study NICU, the rst use of this drug was reported in 2014 and then increased yearly, raising our concern and leading to this work.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its wide bacterial spectrum, including Gram-positive bacteria and its excellent bioavailability, linezolid emerged in the early 2000s as a good alternative to vancomycin. In the specific population of neonates, literature data dealing with linezolid pharmacology, safety, effectiveness and tolerance in neonates is exponential thus demonstrating its growing importance [ 6 , 8 , 9 , 13 ]. In the study NICU, the first use of this drug was reported in 2014 and then increased yearly, raising our concern and leading to this work.…”
Section: Discussionmentioning
confidence: 99%